Biological ageing mediates the associations between urinary metals and metabolic dysfunction-associated steatotic liver disease - Yin-Ping Wu; Jin Feng; Yuan-Yuan Zhang; Bai-Yun Wu; Ze-Hua Zhao; Yu-Chen Fan (Ecotoxicology and Environmental Safety)
Metabolic dysfunction-associated steatotic liver disease (MASLD), which is associated with exposure to heavy metals in the environment, poses a considerable public health challenge globally. We analysed the urinary concentrations of 10 metals, namely, tungsten, cadmium (Cd), molybdenum (Mo), caesium, antimony, cobalt (Co), thallium, uranium (U), lead (Pb), and barium (Ba), in 5205 adults from the National Health and Nutrition Examination Survey. Logistic regression, weighted quantile sum regression, and Bayesian kernel machine regression were used to estimate the associations between urinary metal concentrations and MASLD. The mediating effect of biological ageing on the association between metal exposure and the risk of MASLD was determined using mediation analysis. Ba, Mo, and Co concentrations were found to be positively correlated with the risk of MASLD. Cd, Pb, Co, and U concentrations were positively correlated, while urinary Ba concentration was negatively correlated with phenotypic age and biological age. Biological and phenotypic age were found to be significantly correlated with the occurrence of MASLD. Mediating roles of biological and phenotypic age were found for the associations between urinary concentrations of individual metals (chiefly Co, U, and Cd) and the risk of MASLD, and for the combined effects of multiple metals. In conclusion, metal exposure contributed to the development of MASLD, and this was partially mediated by biological ageing.